2011
DOI: 10.1017/s002193201100006x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Women's Status and Community on the Gender Differential in Children's Nutrition in India

Abstract: This study uses the third National Family Health Survey (2005-06) in India to investigate whether differences in women's status, both at the individual and community levels, can explain the persistent gender differential in nutritional allocation among children. The results show that girls are less likely than boys to receive supplemental food and more likely to be malnourished. In general it appears that higher women's status within a community, as well as higher maternal status, have beneficial effects on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 32 publications
(37 reference statements)
4
63
1
Order By: Relevance
“…On the other hand, Begum & Sen's () analysis of Bangladesh Demographic and Health Survey data did not reveal any statistically significant associations between an aggregated decision‐making autonomy score (which combined autonomy regarding her own health care, child health care, large household purchases, daily household purchases and her freedom to visit relatives and friends) with stunting, wasting or underweight. These findings are consistent with Bose's () results; this recent Indian study used an aggregate autonomy index including decision making on a similar set of aspects (own health care, major household purchases, daily household purchases, visiting family or friends and freedom of movement to market, health facility and outside of village) and found no association with the likelihood of children being underweight (low WAZ).…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, Begum & Sen's () analysis of Bangladesh Demographic and Health Survey data did not reveal any statistically significant associations between an aggregated decision‐making autonomy score (which combined autonomy regarding her own health care, child health care, large household purchases, daily household purchases and her freedom to visit relatives and friends) with stunting, wasting or underweight. These findings are consistent with Bose's () results; this recent Indian study used an aggregate autonomy index including decision making on a similar set of aspects (own health care, major household purchases, daily household purchases, visiting family or friends and freedom of movement to market, health facility and outside of village) and found no association with the likelihood of children being underweight (low WAZ).…”
Section: Resultssupporting
confidence: 90%
“…The key strengths of the WEAI are that it: (i) is the first and only survey-based tool specifically designed to measure women's empowerment in agriculture; (ii) explicitly recognizes the multidimensionality of empowerment; and (iii) includes both a composite index and disaggregated indicators, which allow for a deeper understanding of the relative contributions of different dimensions of (dis)empowerment in a particular context. Greater household decision-making power among women generally fosters improvements in child health and nutrition (42) ; some South Asian studies have shown this positive association (10,11,(13)(14)(15) . In Nepal, maternal input into household decision making has been found to be positively associated with child HAZ (12,13,15,20) , but the relationship has varied by decision-making domain, such as large v. small household purchases, and by nutritional indicators measured (16) .…”
Section: Discussionmentioning
confidence: 99%
“…First, the association may be spurious: the correlation between polygyny and infant mortality may be driven by the fact that polygyny is most common in the poorest, least developed areas of sub-Saharan Africa (Boserup 1985; Jacoby 1995), where the disease burden is high and access to healthcare is limited (Benefo and Schultz 1994; Sastry 1996). Second, if widespread polygyny reflects accentuated institutionalized gender inequalities (Agadjanian and Ezeh 2000; Goody 1973; White and Burton 1988), the broader cultural milieu may produce a direct association between the contextual prevalence of polygyny and infant mortality (Bose 2011; Kravdal 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Highly polygynous settings in sub-Saharan Africa feature greater acceptance of domestic violence and preference for sons across both monogamous and polygynous unions (Cahu, Falilou, and Pongou 2011), offering further evidence that polygyny is bound up with gendered attitudes that are deeply embedded in the local culture and more widespread than the practice itself. Combined with evidence that children in communities where women lack social status and power experience acute health disadvantages (Bose 2011; Kravdal 2004), widespread polygyny may reflect gender inequalities that exacerbate the risk of infant mortality.…”
Section: Introductionmentioning
confidence: 99%